2002
DOI: 10.1026//0012-1924.48.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung eines Messinstrumentes zur Erfassung von Umweltwissen auf der Basis des MRCML-Modells

Abstract: Zusammenfassung. Wissen gilt in der umweltpsychologischen Forschung gemeinhin als ein für ökologisches Verhalten theoretisch bedeutsamer Einflussfaktor. Unhinterfragt blieb bislang jedoch der zur Erfassung von Umweltwissen verwendete Messansatz. Ziel dieser Arbeit ist es, ein Messinstrument - in Form eines Leistungstests auf der Grundlage des Multidimensional Random Coefficients Multinomial Logit (MRCML)-Modells von Adams, Wilson und Wang (1997) - zur Erfassung von Umweltwissen zu entwickeln. Ein Fragebogen mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 17 publications
3
32
1
4
Order By: Relevance
“…Knowledge about environmental issues is thought to be a precondition for meaningful pro-environmental behavior and its transmission is considered a key component and criterion for successful implementation of environmental education programs (UNESCO, 2005; Heimlich and Ardoin, 2008; Kaiser et al, 2008). A moderate, positive influence of domain-specific environmental knowledge has been reported in early research on pro-environmental behavior (Hines et al, 1987) and was replicated in various studies since (Kaiser and Frick, 2002; Frick et al, 2004; Meinhold and Malkus, 2005; Geiger et al, 2014, 2018). Other studies have found very small cross-sectional relationships (Roczen et al, 2013; Braun and Dierkes, 2017; Otto and Pensini, 2017) and the limited use of knowledge interventions on behavior change has been discussed since the seminal paper of Kollmuss and Agyeman (2002).…”
Section: Introduction: the Role Of Knowledge In Pro-environmental Behmentioning
confidence: 63%
See 2 more Smart Citations
“…Knowledge about environmental issues is thought to be a precondition for meaningful pro-environmental behavior and its transmission is considered a key component and criterion for successful implementation of environmental education programs (UNESCO, 2005; Heimlich and Ardoin, 2008; Kaiser et al, 2008). A moderate, positive influence of domain-specific environmental knowledge has been reported in early research on pro-environmental behavior (Hines et al, 1987) and was replicated in various studies since (Kaiser and Frick, 2002; Frick et al, 2004; Meinhold and Malkus, 2005; Geiger et al, 2014, 2018). Other studies have found very small cross-sectional relationships (Roczen et al, 2013; Braun and Dierkes, 2017; Otto and Pensini, 2017) and the limited use of knowledge interventions on behavior change has been discussed since the seminal paper of Kollmuss and Agyeman (2002).…”
Section: Introduction: the Role Of Knowledge In Pro-environmental Behmentioning
confidence: 63%
“…To advance systematic research on the role and structure of environmental knowledge in according behavior, objective instruments are indispensable, even if their development is more complex, as they have to be validated for veridicality, content, uniqueness of correct answers, difficulty levels of adequate distractors (false answer options) or are based on highly ecologically valid simulation tasks (Passafaro et al, 2016). This study contributes to this endeavor with the actualization and advancement of such an instrument based on existing instruments (Kaiser and Frick, 2002; Geiger et al, 2014; Braun and Dierkes, 2017).…”
Section: Introduction: the Role Of Knowledge In Pro-environmental Behmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, IRT modelling allows one to gain valid insights into learners' knowledge and competences and is frequently used in current educational research (e.g., [23][24][25]). However, apart from a few exceptions that have used IRT modelling [26][27][28], most studies evaluating knowledge about Sustainable Development issues did not use IRT-modelling for data analysis. This accounts for studies evaluating knowledge of the SDGs [29], climate change [30][31][32], or biodiversity [33].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive knowledge about environmental issues commonly is regarded as essential to value its context and importance as well as to reach individual behavior dimensions [8]. In environmental psychology research, knowledge is even commonly regarded as a determinant of conservation behavior [9].…”
Section: Introductionmentioning
confidence: 99%